Creación de un brandbook y estrategia digital para el emprendimiento sometech tecnología - Balarezo Prina, Alessandra (2023)
This work focuses on the development of a brand and digital strategy manual for Sometech Technology, a business focused on importing technological products. In addition, the differential advantage is that they have competitive prices according to the market, quality and innovation in their products. The entrepreneurship was growing and they realized that they needed an identity and a digital strategy to be able to position themselves in the market. For this reason, the purpose is the creation of a brand and strategy manual in social networks, because they not only offer technology, but also want to transmit youth, freshness and memorability with the aim of improving customer value. Therefore, the graphic identity created is inspired as the main public by young millennials, in order to create a technological and modern community and take advantage of the import market that is being highly valued.